2021
DOI: 10.3390/ijms221910224
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Dietary Factors as Modulators of the Mucus Layer in Inflammatory Bowel Disease

Abstract: The gastrointestinal tract is optimized to efficiently absorb nutrients and provide a competent barrier against a variety of lumen environmental compounds. Different regulatory mechanisms jointly collaborate to maintain intestinal homeostasis, but alterations in these mechanisms lead to a dysfunctional gastrointestinal barrier and are associated to several inflammatory conditions usually found in chronic pathologies such as inflammatory bowel disease (IBD). The gastrointestinal mucus, mostly composed of mucin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 133 publications
0
11
0
2
Order By: Relevance
“…In addition, diet conditions the composition of the gut microbiota, an aspect that is increasingly associated with the development and evolution of IBD. [ 23 , 24 ] At first glance, wine consumption should be examined as a complex nutritional intervention in UC pathology because of the presence of ethanol, which has been associated with intestinal dysmotility and local inflammation and oxidative stress, amongst other effects. [ 25 ] In addition, the only wine intervention in UC patients reported in the bibliography revealed controversial results, since moderate wine consumption increased gut permeability at the same time that reduced intestinal inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, diet conditions the composition of the gut microbiota, an aspect that is increasingly associated with the development and evolution of IBD. [ 23 , 24 ] At first glance, wine consumption should be examined as a complex nutritional intervention in UC pathology because of the presence of ethanol, which has been associated with intestinal dysmotility and local inflammation and oxidative stress, amongst other effects. [ 25 ] In addition, the only wine intervention in UC patients reported in the bibliography revealed controversial results, since moderate wine consumption increased gut permeability at the same time that reduced intestinal inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the interactions between multi-organs are still ambiguous, which limits the scope of probiotic application. Combined with the complexity of interactions among strains and the complex dietary factors [ 283 ], these difficulties make it hard for us to judge the role played by a specific probiotic in a particular microenvironment. In general, for the development of probiotic therapy, we need to strengthen the basic research related to probiotics, including the mechanism of the interactions between probiotics and different organs, the relationship between probiotics and commensal microorganisms, etc.…”
Section: Challenges and Outlooksmentioning
confidence: 99%
“…The latest study found that dietary thymol reduced the plasma endotoxin and D-lactic acid concentrations on days 7 and 14 post-weaning [ 45 ]. The intestinal mucus layer is the first line of defense maintaining bacterial symbiosis with the host and preventing bacterial penetration into epithelial cells [ 46 ]. Thymol increases mucus secretion to relieve ethanol-induced ulcer mucosal damage in rats [ 47 ].…”
Section: Thymol Protects Intestinal Barrier Function Against Ibdmentioning
confidence: 99%